Reproductive Performance and Larval Quality of First and Second Spawning of Pond-Reared Blue Swimming Crab, Portunus pelagicus, Broodstock - Oniam, Vutthichai; Arkronrat , Wasana (Agriculture and Natural Resources, 2014)
The current was conducted to compare the reproductive performance and larval quality of ﬁ rst (1st) and second (2nd) spawning produced by female blue swimming crab, Portunus pelagicus. The results showed that there were signiﬁ cant differences in several important reproductive parameters and larval quality, 2nd spawning had lower fecundity (508,657 eggs for 1st spawning and 395,118 eggs for 2nd spawning), a lower total number of zoea larvae (259,985 crabs for 1st spawning and 160,900 crabs for 2nd spawning), a lower hatching rate (54.01% for 1st spawning and 41.41% for 2nd spawning) and a lower survival rates of zoea I (87.87% for 1st spawning and 67.19% for 2nd spawning) than 1st spawning. However, the survival rates of the megalopa (30.94% for 1st spawning and 20.29% for 2nd spawning) and ﬁ rst crab stages (1.57% for 1st spawning and 0.85% for 2nd spawning) were not signiﬁ cantly different. Similar crab larval development of 1st and 2nd spawning from the zoea I to megalopa stages (11.2 d for 1st spawning and 11.4 d for 2nd spawning) and the megalopa to ﬁ rst crab stages (4.8 d for 1st spawning and 5.0 d for 2nd spawning) were not signiﬁ cantly different. This study contends that 2nd spawning of female P. pelagicus affected the reproductive performance and survival rates of zoea I.